Similarity Calculation, Enrichment Analysis, and Ontology Visualization of Biomedical Ontologies using UFO. Issue 4 (26th April 2021) - Nguyen, Quang‐Huy; Le, Duc‐Hau
Abstract: The rapid growth of biomedical ontologies observed in recent years has been reported to be useful in various applications. In this article, we propose two main‐function protocols—term‐related and entity‐related—with the three most common ontology analyses, including similarity calculation, enrichment analysis, and ontology visualization, which can be done by separate methods. Many previously developed tools implementing those methods run on different platforms and implement a limited number of the methods for similarity calculation and enrichment analysis tools for a specific type of biomedical ontology, although any type can be acceptable. Moreover, depending on each application, methods have distinct advantages; thus, the greater the number of methods a tool has, the better decisions that users make. The protocol here implements all the analyses above using an advanced popular tool called UFO. UFO is a Cytoscape app that unifies most of the semantic similarity measures for between‐term and between‐entity similarity calculation for biomedical ontologies in OBO format, which can calculate the similarity between two sets of entities and weigh imported entity networks, as well as generate functional similarity networks. The complete protocol can be performed in 30 min and is designed for use by biologists with no prior bioinformatics training. © 2021 Wiley Periodicals LLC. Basic Protocol : Running UFO using a list of input Gene Ontology, Disease Ontology, or Human Phenotype Ontology data